ASTM designation D2357-74 : Standard for qualitative classification of surfactants by infrared absorption. (West Conshohocken (Pa.) : ASTM International)
1.1 This standard covers the qualitative classification of synthetic detergent products or mixtures of synthetic detergents. It is applicable to built detergent formulations as well as individual surfactant compositions. Note 1-The organic active ingredient must be isolated from built syndet compositions in accordance with Test Method D2358.
Keywords: Normen